Eco-friendly, Catalyst-free Synthesis of 2-Amino-2-chromenes in Ionic Liquid [bmim]Br - Davoodnia, A.; Tavakoli-Nishaburi, A.; Behmadi, H.; Tavakoli-Hoseini, N.; Attar, P. (Asian Journal of Chemistry, 2010)
A simple and eco-friendly procedure for the synthesis of 2-amino-2-chromene derivatives using [bmim]Br, a neutral ionic liquid, as an efficient medium without any catalysts has been developed. The present methodology offers several advantages, such as simple procedure with an easy work-up, excellent yields, short reaction times, environmentally benign milder reaction conditions.